Seed germination of the carnivorous plant Byblis gigantea (Byblidaceae) is cued by warm stratification and karrikinolide - Cross, A.; Merritt, D.; Turner, S.; Dixon, Kingsley (2013)
Byblidaceae is one of the most poorly studied carnivorous plant families, with seed dormancy and germination biology remaining unresolved. This knowledge deficit has significant conservation and management implications, particularly as the most southerly distributed species, the south-west Western Australian endemic Byblis gigantea, is listed as critically endangered. This study examined the ecophysiology of seed dormancy and germination in B. gigantea in concert with a study of the population dynamics of a single plant community. Mass seedling emergence and plant establishment were observed after a wildfire in 2007 in the natural population, followed by a rapid decline in mature individuals (91%) over a 4-year monitoring period, with almost no inter-fire recruitment (1.4% of all emergence) observed. Seeds possessed a fully developed embryo, and the germination characteristics of fresh seeds classified them as showing physiological dormancy. Seed dormancy was partially alleviated by warm stratification (30 °C) for 8 weeks prior to incubation at 15 °C, with c. 40% germination observed. With the additional exposure of seeds to the germination-active chemical in smoke, karrikinolide, the germination of warm-stratified seeds increased to 89%. Seeds also displayed orthodox storage behaviour and appeared to be amenable to long-term seed banking for conservation. These results present the first observation of the stimulation of the germination of a carnivorous plant by a smoke-derived compound.